Amygdala Changes Through Breathing Exercise in Coping with the COVID-19 Pandemic - Yuliana, Yuliana (Universitas Terbuka, 2021)
The COVID-19 pandemic brings many psychological and physical changes. In coping with the COVID-19 pandemic, breathing exercise meditation is useful to calm the mind and body. Breathing exercise practice can change the brain, especially amygdala. This paper aims to give insight about amygdala changes through breathing exercise meditation in coping with the COVID-19 pandemic. Methods: This paper is a literature review. Literature was identified from the archives from PubMed, Scopus, and Elsevier. The inclusion criteria were peer-reviewed paper. Keywords were amygdala, breathing, COVID-19, meditation, mindfulness. Results: Breathing exercise meditation and mindfulness practice can increase our awareness and reflections. In the long term, there will be changes in brain structure such as the amygdala. Conclusion: This paper is useful for psychology health knowledge. Patients, individuals, psychologists, physiotherapists, and psychiatrists can apply breathing exercise meditation and mindfulness methods for relaxing to prevent bad brain changes during the COVID-19 pandemic.Ã‚Â